INTEGRATING HISTORY AND SOFTWARE ENGINEERING: A STEM-BASED APPROACH TO TEACHING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The interdisciplinary approach is an effective method in technical education, particularly for integrating humanitarian disciplines with specialised subjects. However, history, philosophy, Ukrainian, and foreign languages often receive minimal teaching hours, leading to insufficient mastery. To address this, we explored the integration of history and culture with technical disciplines, specifically "Modern Programming Paradigms" and "Methods and Systems of Artificial Intelligence," to enhance learning for future software engineers. A STEM project was implemented to explore Ukrainian statehood through engineering solutions and modern technologies. First-year Computer Science students engaged with interactive digital tools, including low-code web application frameworks (Glitch, WordPress), historical data visualisation (Flourish), timeline and mapping tools (TimelineJS, StoryMapJS), and interactive presentations (Canva, Google Slides). The project’s effectiveness was assessed using a rubric-based evaluation with three key criteria: content, technology, and collaboration. The analysis showed no statistically significant differences between teams (p > 0.05), indicating consistent engagement. The highest score was in "Collaboration" (3.47), demonstrating effective teamwork. The "Technology" criterion (3.23) reflected satisfactory proficiency in software tools, while "Content" scored the lowest (2.73), highlighting challenges in integrating historical narratives with programming. Correlation analysis showed a weak relationship between criteria, meaning technical skills did not necessarily translate into high-quality content or teamwork. A SWOT analysis based on an anonymous student survey provided direct feedback for improving future STEM projects. Key advantages included deeper assimilation of historical facts, practical application of programming skills, and teamwork experience. However, students noted limited time for mastering content and a lack of necessary equipment as challenges. These findings highlight the need to strengthen the historical component and improve programming integration with humanities for a more comprehensive learning experience.